New phenomena and trends in Chilean politics - L. V. Diyakova (Ибероамериканские тетради, 2019)
The article analyzes new phenomena and trends in Chilean politics, the results of the first period of activity of the center-right government ofS. Pinera, who came to power in 2018. The main attention is paid to the analysis of contradictory initiatives of the government aimed at increasing economic efficiency at the expense of social expectations. It is noted that the greatest risks are associated with the deepening crisis in relations between the government and society, the activation of the radical protest movement caused by the unsuccessful attempt to raise prices for the subway. This measure led to mass youth protests in October 2019, clashes with police and the imposition of a state of emergency, which was accompanied by an appeal of the government to help of the army. The result of the severe political crisis was the resignation of the Cabinet and the announcement of a new package of social reforms. Among the new political phenomena, the author also highlights the decline of traditional center-left, the collapse of the coalition New majority, the beginning of the institutionalization of leftist party alternative to the official center-left, and strengthening the ultra-conservative wing on the right flank.